Pengaruh Penggunaan Media Pembelajaran Aplikasi Wordwall Terhadap Kemampuan Literasi Siswa SD Negeri 1 Selanegara - Nugraha, Izqi Firoza Gusma; Azizah, Amalia Nurul; Kurniawan, Alfi Muklis (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of using the Wordwall learning media application on the literacy skills of students at SD Negeri 1 Selanegara. This research uses a quantitative method with a pre-experimental design (one group pretest-posttest design). The sample of the study consists of 13 fourth-grade students. The instruments used include a literacy test (pretest with 40 questions and posttest with 20 questions) and a questionnaire on implementation. The data analysis technique used is the t-test (paired sample t-test). The research results show an increase in the average literacy scores of students after learning using Wordwall, from an average pretest score of 66.54 to an average posttest score of 74.23. The t-test results indicate a significance value of < 0.05, which means there is a significant effect of using Wordwall on students' literacy skills. Thus, the Wordwall media has proven to be effective and can be used as an innovative alternative to improve the literacy of elementary school students.